TEACHER POSITION FOR PROMOTING AUTONOMOUS LEARNERS IN TEACHING SPEAKING ENGLISH - Welly Kuswanto; Khoirul Anwar (DIDAKTIKA, 2014)
In teaching speaking English, teacher has high contribution for promoting autonomous learners. Autonomous learner refers to someone who has the capacity to take control of one self involving self-management, self direction and self evaluation. To promote autonomous learners when teaching speaking English, teacher must design all materials and implement it by nine strategies. The nine strategies are setting objectives, selection of materials, methods, teacher's role, teacher-learner relationship, learning environment, homework, presentation and talks, and evaluation. By applying the nine strategies will place the teacher on the right position as facilitator to support autonomous learners in teaching speaking English.